Signifikansi Unsur Budaya Lokal dalam Film Horor Mangkujiwo (2020) - Paulus Heru Wibowo Kurniawan; Bisma Fabio Santabudi (Sense: Journal of Film and Television Studies, 2023)
The background of this research is that elements of local culture that are sociologically manifested in symbols, language, beliefs, values, and cultural artifacts are often used as settings in the narrative structure of films. In contemporary Indonesian horror films, local cultural elements have begun to be considered, but are often not seen as an important part of a complete narrative. Therefore, this research wants to explore the importance of local cultural elements in an Indonesian horror film entitled Mangkujiwo (2020). The type of research used is qualitative research by utilizing John Fiske's semiotic method which is used as a means to understand conceptual relationships that produce explicit meanings that are objective. The results show that the significance of local cultural elements presented in the horror film forms 5 patterns that are closely related to belief in myths and magi and the Kejawen mystical system, the role of shamans in the mystical practices of Javanese society, property and throne as markers of power, revenge as the achievement of just conditions, and family as the site of tragedy